APEC early voluntary sectoral liberalisation - Dee, Philippa S. (Staff research paper., 1998)
This paper examines the likely long-term of elected EVSL initiatives. It finds that, while the broadly-based nominations are likely to lead to real income gains for a majority of APEC members, some more narrow nominations could generate significant economic losses. The paper examines a range of modifications to the food proposal which could eliminate such problems.